The Happy Farmer: The Effect of Nonpecuniary Benefits on Behavior. (12th May 2015) - Howley, Peter
Abstract : I test empirically the relationship between farmers' perceptions of the nonpecuniary benefits from farming with a variety of field behaviors such as disinvestment, production, diversification, and off‐farm labor market participation. Results suggest that nonpecuniary benefits have an important influence on a wide range of farmer activities. While costs and returns are clearly important, I suggest that nonpecuniary benefits may make some choices more attractive than others which may be more rewarding financially.